2014
DOI: 10.1007/s00586-014-3597-z
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ expectations of lumbar spine surgery

Abstract: There were wide variations in expectations among patients. Multiple demographic, psychological, and clinical characteristics were associated with expectations, with disability due to pain being the most consistently associated variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 26 publications
4
54
1
Order By: Relevance
“…Consequently, one should adjust for the baseline score when using such outcome criteria in clinical trials and risk factor analyses. A possible cause might be higher expectations towards improvements among patients with high baseline pain and disability [42]. Fulfillment of expectations has also been identified as a major predictor for positive patient-rated positive outcome after surgery [35].…”
Section: Methodological Challengesmentioning
confidence: 99%
“…Consequently, one should adjust for the baseline score when using such outcome criteria in clinical trials and risk factor analyses. A possible cause might be higher expectations towards improvements among patients with high baseline pain and disability [42]. Fulfillment of expectations has also been identified as a major predictor for positive patient-rated positive outcome after surgery [35].…”
Section: Methodological Challengesmentioning
confidence: 99%
“…The methodological characteristics of the articles found are similar, with 16 observational studies (9)(10)(13)(14)(18)(19)(20)(21)(22)24,26,(30)(31)(32)(33)(34) ; six prospective cohorts (25,(27)(28)34,(36)(37) ; one retrospective cohort (38) , one quasi-experimental study (35) , and one experimental study (29) . The use of instruments occurred in the immediate preoperative period in 21 studies that assessed patients' expectations (10,14,(18)(19)(20)(21)(22)(23)(24)(25)(26)(28)(29)(30)(31)(32)(33) , whereas in two studies it occurred when the patient received the indication of surgical treatment (9,27) , one study used them in the intermediate preoperative period (13) ; finally, one study completed the instrument after the patient underwent a spine surgery (34) . Three catego...…”
Section: Resultsmentioning
confidence: 64%
“…The studies were published between 1998 and 2015 and, in general, publications on this subject increased in the last five years (9)(10)14,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) . The methodological characteristics of the articles found are similar, with 16 observational studies (9)(10)(13)(14)(18)(19)(20)(21)(22)24,26,(30)(31)(32)(33)(34) ; six prospective cohorts (25,(27)(28)34,(36)(37) ; one retrospective cohort (38) , one quasi-experimental study (35) , and one experimental study (29) . The use of instruments occurred in the immediate preoperative period in 21 studies that assessed patients' expectations (10,14,(18)(19)(20)(21)(22)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mancuso et al [1] performed an in-depth study of patients' expectations in lumbar spine surgery on a large number of individuals and were able to isolate factors influencing their expectations. Of course, like for any study there were limitations and they duly reported them.…”
mentioning
confidence: 99%